Effects of TRX suspension training on proprioception and muscle strength in female athletes with functional ankle instability übersetzter Titel (DE) - Khorjahani, A.; Mirmoezzi, M.; Bagheri, M.; Kalantariyan, M. (Asian Journal of Sports Medicine, 2021)
Background: Functional ankle instability (FAI) is a common consequence of ankle sprain injury, especially in high-impact sports.